2019
DOI: 10.1590/1982-0194201900059
|View full text |Cite
|
Sign up to set email alerts
|

Construção e validação de conteúdo de cartilha educativa para prevenção de quedas no hospital

Abstract: Resumo Objetivo Construir e validar cartilha educativa para prevenção de quedas no hospital. Métodos Estudo metodológico desenvolvido a partir da construção, validação e avaliação da cartilha por 22 enfermeiros e 22 pacientes internados em clínica médica. Para a validação com juízes, avaliou-se objetivo, estrutura/apresentação e relevância do material e, na avaliação com pacientes, aplicou-se o instrumento Suitability Assesment of Materials (SAM). Utilizou-se o Índice de Validade de Conteúdo (IVC) para aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 17 publications
3
10
0
17
Order By: Relevance
“…Finally, they recommended that some unnecessary images in the booklet be removed and that more images be added to some sections to understand the text better. Kitching also believed that images cannot always help learning [33] and should only help understand essential information [34]. Excessive or inappropriate use of images can distract the reader from the text, but low and appropriate use can be attractive and encourage the reader to read the text [18].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they recommended that some unnecessary images in the booklet be removed and that more images be added to some sections to understand the text better. Kitching also believed that images cannot always help learning [33] and should only help understand essential information [34]. Excessive or inappropriate use of images can distract the reader from the text, but low and appropriate use can be attractive and encourage the reader to read the text [18].…”
Section: Discussionmentioning
confidence: 99%
“…46 The use of figures associated with text makes the educational material of adequate understanding during reading. 47 Regarding the motivation dimension, one of the items did not reach validation, concerning the possibility of the technology produced to promote behavior and attitude change among the nursing mothers during the breastfeeding process. In fact, this limitation had been pointed out by some participating judges and also finds support in other studies of educational material validation, which in turn found similar results.…”
Section: Dimensions Of the Content Validation Toolmentioning
confidence: 99%
“…Essa pesquisa foi desenvolvida de acordo com as seguintes etapas: 1) Levantamento bibliográfico; 2) Construção da tecnologia educativa; e 3) Validação do conteúdo e aparência por especialistas em diabetes e produção técnica, baseando-se em pesquisas semelhantes (9)(10) , que também buscaram seguir as mesmas etapas no trabalho de construção e validação de suas tecnologias educativas em saúde.…”
Section: Métodosunclassified